Meu jogo de memória de Natal - Schmidt, Ana Paula Carvalho; Thomazine, Angelica Micoanski; Fernandes, Bárbara de Paula; Bisognin, Eduarda Victória (Notas de Pesquisa, 2024)
Não se aplica ao Plano de ensino.